Monitoring of organochlorine pesticide residues in school milk and associated health risk assessment in Thailand - Cha-aim, Chatartorn; Manamoongmongkol, Kanjana; Nisapai, Wiparat; Phumjan, Lamphung; Oomnog, Niroth; Kaewlaoyoong, Acharee; Suwapanich, Rachit; Sriprom, Pongsert (My University, 2026)
School milk products are recognized as an important and affordable food source for Thai people, particularly students. However, milk was classified as an agricultural product in which organochlorine pesticide (OCP) residues can be detected due to its fat content. This study investigated the levels of organochlorine pesticides in school milk products, including raw milk, pasteurized milk, and UHT milk, using the QuEChERS method. The fat content of these three types of milk was 3.50%, 3.03%, and 3.33%, respectively. A correlation coefficient (R2) of 0.9953–0.9998 confirmed the validity of the QuEChERS method. The limit of detection (LOD) for each pesticide ranged from 0.003 to 0.0615 mg/kg, and the limit of quantification (LOQ) ranged from 0.010 to 0.2050 mg/kg, with recovery rates of 80.95–110.00%. The analysis for 13 organochlorine pesticide residues, including Aldrin, Cis-Chlordane, Trans-Chlordane, Dieldrin, p,p'-DDD, p,p'-DDE, p,p'-DDT, Endrin, Heptachlor, Heptachlor epoxide, alpha-HCH, beta-HCH, and gamma-HCH using a GC–MS, revealed that no residues were detected above the LOQ (0.01 mg/kg) in any samples, indicating compliance with food safety standards. A scenario-based risk assessment using estimated daily intake (EDI) and hazard quotient (HQ) suggested that, although current exposure is negligible, potential risks may arise under worst-case conditions, particularly for aldrin, dieldrin, and heptachlor in high-consumption groups. Overall, school milk products in Thailand are considered safe; however, continuous monitoring and risk assessment remain essential to ensure long-term food safety.
Keywords: OCPs; Organochlorine pesticides; QuEChERS method; Risk assessment; School milk